Topical Curcumin: A Review of Mechanisms and uses in Dermatology - Heng MCY (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2017)
Curcumin, the active ingredient in the spice turmeric, has been used in many Eastern countries for its known anti-infl ammatory activity. Recently, analysis of multiple studies have cast doubt with regard to the effi cacy of oral curcumin in several diseases. While the effectiveness of oral curcumin is hindered  by its low bioavailability and poor absorption by the oral route, this is not the case for topical curcumin. In this review, we discuss the mechanisms for its anti-infl ammatory and anti-apoptotic activity based on its inhibitory activity on the enzyme, phosphorylase kinase, and present evidence for its salutary effects on burns, wounds, surgical scars, photo-damaged skin and psoriasis.